(3GdEOGQI GdMOjKI ddeNGRf hGdeTJQjGJ (B:s (3EOGQI SdSdI GdJhQjO (B/s - (3GdYdi, YHO GdSJGQ eMeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2006)
(3eaghe hWHjYI GdeNRhf(B-(3GdeSJhOYGJ(B-(3Jbjje hbjGS GdeNRhf(B-(3feGPL GdeNRhf GdEbJUGOj(B-(3CfhGY GdWdH hCfXeI GdTQGA(B-(3GdeTJQjGJ(B-(3JNWjW GdeJWdHGJ GdeGOjI(B-(3fXGe GdLOhdI GdBfjI(B-(3EOGQI GdehGQO hGdJRhjO(B-(3EOGQI SdSdI GdJhQjO(B-(3eNRhf GdehGO JMJ GdUfY hfXQjI GdbjhO(B-(3EOGQI GdLhOI GdTGedI hEOGQI GdehGOs
Keywords: (3EOGGQI GdeTJQjGJs; (3EOGQI GdeNGRfs